Construction of a transit network simulation platform - Yang, Wei (Nanyang Technological University, 2020)
This report details the process of the construction of a realistic transit network simulation platform, taking reference in the Jurong west region, particularly the Boon Lay/ Pioneer area. It features two public transport (Bus) routes in the region. The software used to construct the simulation platform for this project is PTV VISSIM. It is a world leading traffic planning tool which can simulate complex vehicle intereactions on a microscopic level. It also uses a dynamic vehicle assignment approach to simulate the randomality of traffic flow to increase the platform’s realisticality. Vissim also provides a diverse array of tools and parameters such as isolated signal group controllers, designated vehicle route and vehicle speed variations to make the simulation as realistic as possible. Apart from the construction of a realistic transit networkl platform, this report also further explores various signal control strategies in hopes to improve the delay and travel time of the bus services.